GTFS-VIZ: Tool for preprocessing and visualizing GTFS data - Narumon Kunama (2018)
© 2017 Association for Computing Machinery. This paper presents a tool called GTFS-Viz for preprocessing and visualizing General Transit Feed Specification (GTFS) data. GTFS data is a common format for the public transportation schedules with associated geographic information. The tool consists of two main parts: preprocessor and visualizer. The preprocessor retrieves and transfers the GTFS data into a new data format for the visualizer. The visualizer displays an animation of public transport movement according to its schedule specified in the GTFS data on a map. It also displays a graph of the number of public transport vehicles per hour, and allows the user to choose a specific transport route, trip, and stations to visualize. This is the first attempt to build a tool that preprocesses and visualizes GTFS data that is publically available in a format that is not so easy to process with existing standard data visualization tools.